Seleção de genótipos de limão - Martires, Augusto Malaguti Braghini Marcolini (Universidade Federal de São Carlos, 2024)
For the advancement of the citrus sector and the improvement of producers' profits in the national territory, the search for new varieties of citrus in the current Brazilian scenario is deeply essential. Several varieties of lemons (Citrus limon (L.) Burm) can be commercialized, either for fresh consumption and for industrial processing, depending on the agronomic characterization of each variety. The objective of this work was to evaluate fruits and plants present in the BAG (Active Citrus Germplasm Bank) that is present in Sylvio Moreira Citriculture Center/IAC, seeking to identify new genotypes with commercialization potential. The work was conducted at the “Sylvio Moreira” Citriculture Center/IAC (CCSM/IAC), whose institution maintains the largest and most important citrus collection in the world at BAG. Among the accessions available at BAG, in 2019, eight lemon varieties were selected (Kutdiken SRA 530, Fino SRA 344, Asaasli SRA 632, Kerkachi IAC 694, Karystine SRA 623, Malti SRA 636, Lapithou SRA 541 and Menton SRA 625). Two seedlings were made from these varieties, grafted onto Rangpur lime, which were planted in an experimental field orchard. In 2022, physical-chemical analyzes of the fruits were carried out (juice yield, total soluble solids, total titratable acidity and proportion), number of seeds per fruit and vegetative development of the plants (height, diameter and crown volume). Juice yield showed no difference between the evaluated genotypes. The juice from the Kerkachi IAC 694 genotype showed lower total titratable acidity, a higher number of soluble solids and a higher proportion compared to the other genotypes. Regarding the number of seeds per fruit, the Kutdiken SRA 530 genotype presented the lowest number of seeds per fruit when compared to other genotypes. All trained genotypes were vigorous, this can be seen from the height, diameter and crown volume of the plants of all genotypes, which have values equal to or greater than 3.1 meters, 3.3 meters and 19.76 meters, respectively, at the end of the third year of planting, revealing robust and healthy development. All evaluated genotypes are options available for the fresh fruit market. The quantity of genotype seeds is within acceptable parameters, highlighting the adaptability of these materials to market demands and highlighting their potential to meet expected quality standards.
Selection of lemon genotypes
Keywords: Frutos; Suco; Ratio; Sementes; Fruits; Juice; Seeds; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA